Personal Hygiene Ibu Dengan Kejadian Diare Pada Balita di Wilayah Kerja Puskesmas Bajoe Kabupaten Bone - Erlani, Erlani; Amir, Egit Triayu Prayuni; Khaer, Ain (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Diarrhea is an environmental-based disease that is still a common health problem in developing countries, including Indonesia, caused by several factors, one of which is the hygiene behavior factor. Diarrhea is more dominant in toddlers because their immune systems are still weak, so toddlers are very susceptible to the spread of bacteria that cause diarrhea. The purpose of this study was to determine the relationship between maternal personal hygiene and the incidence of diarrhea in toddlers in the Bajoe Health Center work area, Tenete Riattang Timur District, Bone Regency. This study was an observational analytic study with a Case Control approach, namely a research method used to investigate or examine risk factors that potentially affect disease cases. The results of the study showed that there was a relationship between the habit of washing hands with soap and the incidence of diarrhea in toddlers (p = 0.004 <0.05), there was a relationship between nail cleanliness and the incidence of diarrhea in toddlers (p = 0.044 <0.05), and there was a relationship between Exclusive Breastfeeding and MPASI with the incidence of diarrhea in toddlers (p = 0.042 <0.05). Conclusion: There is a significant relationship between the habit of washing hands with soap, cleanliness of the mother's nails, and the provision of exclusive breastfeeding and complementary feeding with the incidence of diarrhea in toddlers at the Bajoe Health Center, Bone Regency. It is recommended that the government, in this case by health workers, always socialize policies, persuasion, and education on clean and healthy living behavior by getting used to washing hands with soap, nail cleanliness and paying more attention to the parenting patterns of toddlers in terms of providing exclusive breastfeeding and complementary feeding. Keywords: Diarrhea; Personal Hygiene;Toddler